2017
DOI: 10.21831/economia.v13i2.14980
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Kualitas Reviu Dan Implikasinya Terhadap Kualitas Laporan Keuangan Pemerintah Daerah

Abstract: Abstrak: Determinan Kualitas Reviu dan Implikasinya terhadap Kualitas Laporan Keuangan Pemerintah Daerah. Penelitian ini bertujuan untuk menjelaskan pengaruh dari kompetensi, komitmen organisasi dan sistem pengendalian intern (SPI) terhadap kualitas reviu dan implikasinya terhadap kualitas Laporan Keuangan Pemerintah Daerah (LKPD). Reviu dalam hal ini adalah reviu LKPD. Penelitian ini menggunakan analisis regresi linier berganda untuk menguji pengaruh kompetensi, komitmen organisasi dan sistem pengendalian int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Based on these objectives, the role of the Inspectorate is significant in realizing quality LKPD and in accordance with accrual-based SAP. This is also in line with the results of the study (Maulana, Djamhuri, & Purwanti, 2017) which concluded that quality review had an effect on the quality of the LKPD.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on these objectives, the role of the Inspectorate is significant in realizing quality LKPD and in accordance with accrual-based SAP. This is also in line with the results of the study (Maulana, Djamhuri, & Purwanti, 2017) which concluded that quality review had an effect on the quality of the LKPD.…”
Section: Introductionsupporting
confidence: 90%
“…Previous research related to the implementation of a review by the Inspectorate carried out by (Bekaiang et al, 2017) and (Widyarini et al, 2016) showed that the review procedure had a significant effect on the quality of local government financial report review. Subsequent research by (Maulana et al, 2017) proves that the quality of the LKPD review influences the quality of financial statements and is influenced by competencies, organizational commitment, and the entity's internal control system.…”
Section: Review Of Government Financial Reportsmentioning
confidence: 99%